2002
DOI: 10.1111/j.1365-2621.2002.tb09428.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Time on Volatile Compounds, Odor, and Flavor of Cooked Beef from Pirenaica and Friesian Bulls and Heifers

Abstract: Volatile compounds, odor, and flavor produced by beef from bulls and heifers of the Pirenaica and Friesian breeds were studied during 7 d of aging. The Friesian breed beef had stronger fatty flavor and aftertaste than the Pirenaica, as well as differences in the content of several volatile compounds. Bull beef had stronger liver-like odor and flavor, and bloody flavor that were related to a higher 2-propanone content, while beef from heifers had stronger characteristic flavor. Aging of meat increased character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 19 publications
5
75
2
8
Order By: Relevance
“…In general, these values agree with results from other research works carried out in beef samples from Pirenaica and Friesian breeds (Lizaso, 1998;Alzueta, 2000;Alberti et al, 2005;Goñ i et al, 2007). Regarding volatile compounds, area values in this study were higher than the values reported by Gorraiz et al (2002). The differences may be attributed to quantifying volatile compounds by gas chromatography v. mass spectrometry.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In general, these values agree with results from other research works carried out in beef samples from Pirenaica and Friesian breeds (Lizaso, 1998;Alzueta, 2000;Alberti et al, 2005;Goñ i et al, 2007). Regarding volatile compounds, area values in this study were higher than the values reported by Gorraiz et al (2002). The differences may be attributed to quantifying volatile compounds by gas chromatography v. mass spectrometry.…”
Section: Resultssupporting
confidence: 91%
“…The significant correlation between TBA and the above-mentioned volatiles and the fact that these compounds were tentatively identified in all these samples would let us infer that these volatile compounds might be used as raw beef quality degradation markers. Among those evaluated, 2-propanone was predominant in the profile of raw beef and also in cooked beef (MacLeod and Ames, 1986;Gorraiz, 1999). In addition, the decrease in DMS was proposed as a marker of the degradation of raw beef quality by Insausti et al (2002).…”
Section: Resultsmentioning
confidence: 98%
“…Table 1 shows that the cattle used in this study produced medium-high conformed and low-fat carcasses: conformation score U or 'very good' and fatness score 2 or 'slight'. Data from the carcasses studied (Table 2) could be a representative sample of Pirenaica young bulls raised and slaughtered similarly, because they were similar to those reported for different authors (Goñ i et al, 1999;Gorraiz et al, 2002;Alberti et al, 2005). Table 3 lists the colour coordinate values characterizing the subcutaneous fat, LTD and RA muscles on the day of slaughter (45 min post slaughter) and after chilling for 24 h. The results for the colour coordinates a* and b* for the RA muscle in this study are similar to those described by Klont et al (1999) and Lagoda et al (2002).…”
Section: Resultssupporting
confidence: 67%
“…Meat obtained from bulls is characterized by a stronger liver-like and rare (bloody) odor compared to the meat of heifers. It is linked with the content of such volatile compounds as: hydrocarbons, aldehydes, alcohols and ketones (Gorraiz et al, 2002). Beef produced from cattle of Wagyu breed is more flavored than the meat obtained from dairy breeds.…”
Section: Factors Affecting Changes In Volatile Compoundsmentioning
confidence: 99%